Analisis Pengalaman Sensorik dan Implikasinya Terhadap Pemasaran Desa Wisata - Mustaqim, Hadi Ichsan; Diyah Setiyorini, Heri Puspito; Khaerani, Rijal (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
Tourism villages are a rapidly growing segment in tourism, offering authentic cultural experiences. To enhance these experiences, the concept of sensory marketing offers a robust framework; however, its application within the context of heritage-based tourism villages remains limited. This study aims to conduct an in-depth analysis of the sensory experiences of tourists in Sade Tourism Village and explore their implications for marketing strategies. Using a qualitative approach with a phenomenological method, this study explores the meaning of the lived experiences of 18 participants, comprising both tourists and managers. Data were collected through in-depth interviews and analyzed thematically to identify patterns and the essence of their experiences. The findings indicate that the tourist experience in Sade Village is dominated by the senses of sight (unique architecture) and touch (the experience of trying weaving). Conversely, the auditory and olfactory experiences are not consistently perceived, while the gustatory (culinary) experience is the weakest and most inadequate. From a marketing perspective, the village's strategy was found to be organic but lacked strategic planning. To optimize its marketing, heritage-based tourism villages cannot rely solely on visual authenticity but must consciously manage and integrate all five sensory dimensions to create a holistic, memorable, and sustainable experience.